Axial and lateral crushing of the filament wound laminated composite curved compound system - Mahdi, E.; Hamouda, A.M.S.; Sahari, B.B. (Informa UK Limited, 2002)
In this paper, experimental and numerical investigations into the crushing behaviour of the filament wound laminated curved compound system have been conducted. The structure being investigated is composed of a complete and semi-circular cone-cylinder-cone system. The conical parts of the structure were symmetric. The cone vertex angle and the cylindrical part height were 15 degrees and 10 mm, respectively. Load-displacement curves and deformation histories of typical specimens are presented and discussed. The experimental data are correlated with predictions from finite element model. Numerical results show that for curved systems under lateral load, local stress has been concentrated at the junctions between the cylinder and cones as well as the edge of the systems, while for the curved systems under axial load, the stress concentration is slightly clear at the loaded end of the curved systems. Experimental results show that the axial loaded curved systems are crushed into a progressive failure mode and exhibit high-energy absorption capability. Results also show that the debonding at the fibre-matrix interface is influenced by the load-displacement relationship for the lateral loaded curved systems. On the other hand, the fragmentation failure mode is dominated by the load-displacement relationship for the axial loaded curved systems.